INFORMATION SYSTEMS FOR SMALL AND MEDIUM-SIZED ENTERPRISES BY VOSMIL 1.0 APPLICATION AT CV. KREASI KONCONE NGEMIL - Putri Nugrahaningsih; Labbaika Dwi Ayu Rahmawati; Denty Arista; Zaim Arif Eko Saputro (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Currently, quite a lot of Micro, Small, and Medium Enterprises (MSMEs) are experiencing difficulties in increasing their business significantly. One of them is CV. Koncone Ngemil. After being traced, they have difficulty recording financial transactions well and do not understand digital bookkeeping and financial reports. Meanwhile, they already have many work partners, with around 70 partners spread from Surakarta to Yogyakarta. This research is qualitative research using the FGD technique in data collection. The presence of the MSME Accounting Information System (AIS), especially the VOSMIL 1.0 application, is a means to compile various reports that are needed digitally. This community service activity aims to provide knowledge and guidance to CV. Koncone Ngemil to be able to record financial reports digitally using the VOSMIL 1.0 application so that they can improve their business significantly. The results show that using the Vosmil 1.0 application provides convenience to CV. Koncone Ngemil in digital financial records.